The ATS on the Web: Introducing Modem Information Technology in Antarctic Affairs - Vidas, Davor; Njåstad, Birgit (Implementing the Environmental Protection Regime for the Antarctic, 2000)
Keywords: Antarktis; Antarktistraktaten; miljøprotokollen; miljøvern

Emerging Law of the Sea Issues in the Antarctic Maritime Area: A Heritage for the New Century? - Vidas, Davor (Ocean Development & International Law, 2000)
This article focuses on three emerging law of the sea issues for states cooperating in management of the Antarctic and its maritime area. The first of these is no newcomer: How to regulate the dramatic increase in illegal, unregulated and unreported fishing of Patagonian toothfish (Dissostichus eleginoides) in the Southern Ocean? The second question, according to the letter of the UN Convention on the Law of the Sea, awaits the countries claiming sovereignty over portions of territory in the Antarctic 10 years from the entry into force of the Convention for each of them. The question here is what to do with the requirement contained in that Convention relating to the submission of information on the outer limit of the continental shelf beyond 200 nautical miles to the Commission on the Continental Shelf? Finally, there is a third tricky question: Who is competent to regulate, and accordingly to ban, mineral activities in the Southern Ocean seabed? Is it the International Seabed Authority as the global body, or the Antarctic Treaty Consultative Parties through their regional cooperation? This question may well never be put on the policy agenda for any global forum; but it may well be posed at any time and by any third party, whether in the UN General Assembly or, more likely, in the Assembly of the International Seabed Authority.
Publisher: Taylor & Francis
Keywords: Antarktis; Antarktistraktaten; Sørishavet; fiskeri; havrett; internasjonal rett; kontinentalsokkel

The protocol on environmental protection to the Antarctic Treaty: a ten-year review - Vidas, Davor (Yearbook of international co-operation on environment and development, 2002)
Keywords: Antarktis; jus; miljøvern

Protecting the polar marine environment : law and policy for pollution prevention - Vidas, Davor (ed.) (Cambridge University Press, 2000)
Keywords: Antarktis; forurensning; hav; miljørett; miljøvern; polarområdene; skadeforebygge

The Committee for Environmental Protection: Its Establishment, Operation and Role within the Antarctic Treaty System - Orheim, Olav (Implementing the Environmental Protection Regime for the Antarctic, 2000)
Keywords: Antarktis; miljø; miljøkonsekvensanalyser; miljøpåvirkning

Norway: Implementing the Protocol on Environmental Protection - Njåstad, Birgit (Implementing the Environmental Protection Regime for the Antarctic, 2000)
Keywords: Antarktis; Antarktistraktaten; miljøprotokollen; miljøvern